2019
DOI: 10.2478/rtuect-2019-0057
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency Obligations and Subsidies to Energy Intensive Industries in Latvia

Abstract: The European Union’s climate and energy policy for 2030 sets ambitious targets and will challenge current energy use patterns. At the same time, policy objectives are to maintain energy affordable for business and consumers, which means that energy and climate goals should be achieved in the most cost-effective way. There is a well-known energy efficiency gap between effectively implemented energy efficiency measures and potentially economically viable ones. The authors have made a statistical analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, subsidies work well when applied to market-ready technologies that are prepared to move from prototype to mass production. Subsidies aim to reduce technology costs, demonstrate technological feasibility, identify potential market barriers and increase market penetration [5]. These instruments can be converted into loans or investments if the renewable energy technology is commercially successful.…”
Section: Introductionmentioning
confidence: 99%
“…However, subsidies work well when applied to market-ready technologies that are prepared to move from prototype to mass production. Subsidies aim to reduce technology costs, demonstrate technological feasibility, identify potential market barriers and increase market penetration [5]. These instruments can be converted into loans or investments if the renewable energy technology is commercially successful.…”
Section: Introductionmentioning
confidence: 99%
“…In previous publication [33] authors concluded that manufacturing of wood and wood products is significantly affected by certain subsector C1629, which should be analysed separately. European and national statistical offices are not providing energy consumption data of industries on a subsectors level, therefore, in this study, the authors calculated energy consumption of subsector C1629 using 3-year average energy costs as a proxy.…”
Section: Resultsmentioning
confidence: 99%
“…The model could be calibrated and used as a tool for policymakers to develop sector specific legislation and requirements related to energy management practices. As a result, more efficient policy instruments could be developed in order to increase the industry engagement towards the implementation of the energy efficiency activities [27].…”
Section: Discussionmentioning
confidence: 99%